Functional ability in a population: normative survey data and reliability for the ICF based Norwegian Function Assessment Scale - Natvig Bård; Benth Jurate; Garratt Andrew; Brage Søren; Østerås Nina; Gulbrandsen Pål (BMC, 2007)
Abstract Background The increasing focus on functional ability assessments in relation to sickness absence necessitates the measurement of population functional levels. This study assessed the reliability of the Norwegian Function Assessment Scale (NFAS) and presents normative population data. Methods All inhabitants in seven birth cohorts in Ullensaker municipality in 2004 were approached by means of a postal questionnaire. The NFAS was included as part of The Ullensaker Study 2004. The instrument comprises 39 items derived from the activities/participation component in the International Classification for Functioning, Disabilities and Health (ICF). Based on the results of principal component analysis, these items comprise seven domains. Non-parametric tests for independent samples were used to compare subgroups. Internal consistency was assessed by Cronbach's alpha. Two-week test-retest reliability was assessed by total proportions of agreement, weighted kappa, and intraclass correlation coefficient (ICC). Results The response rate was 54% (1620 persons) and 75.4% (101 persons) for the retest. Items had low levels of missing data. Test-retest reliability was acceptable with high proportions of absolute agreement; kappa and ICC values ranged from 0.38 to 0.83 and 0.79 to 0.83, respectively. No difficulty on all 39 functional activities was reported by 33.1% of respondents. Females, older persons and persons with lower levels of education reported more functional problems than their respective counterparts (p < 0.05). The age gradient was most evident for three of the physical domains. For females aged 24-56 and males aged 44-76, a clear education gradient was present for three of the physical domains and one mental domain after adjusting for age and gender. Conclusion This study presents population based normative data on functional ability, as measured by the NFAS. These data will serve as basis for the development of national population norms and are necessary for score interpretation. Data quality and test-retest reliability of the NFAS were acceptable.